Territory Management: Urban Planning and Recreational Planning of Populated Areas in the Republic of Kazakhstan in the Second Half of the 20th Century - KORNILOVA, Alla Aleksandrovna; KHOROVETSKAYA, Yevgeniya Mikhaylovna; MAMEDOV, Seimur Etibarogly; OSPANOV, Timur Zhanatovich; SARSEMBAYEVA, Dinara Yerzhanovna (Journal of Environmental Management and Tourism; Vol 10 No 6 (2019): JEMT Volume X Issue 6(38) Fall 2019, 2019)
The aim of the work is to determine the principles for the formation of urban planning and tourist and recreational zones in the territories of the Republic of Kazakhstan (Kazakh SSR) in the second half of the 20th century. Particular attention is paid to rural populated areas. It was revealed that the architectural and planning decisions that emerged during the period of intensive development of the Kazakh SSR laid the foundation for the development of populated areas, which was reflected in the modern standards for regulating the development of urban and rural settlements in modern Kazakhstan. According to the results of the conducted study, a conceptual and theoretical model of the formation of the architectural and planning structure of populated areas was developed, the main components and principles of its formation were identified, and prognostic trends of its use were determined.